Social media and body dissatisfaction in young adults: An experimental investigation of the effects of different image content and influencing constructs - Castellanos Silva, Raquel; Steins, Gisela (Frontiers in Psychology, 2023)
Research shows negative correlations between media exposure of body images in the context of hegemonic beauty ideals and body satisfaction. The present study deals with the underlying mechanisms and the effects of different exposure contents. In the online experimental study, a sample consisting of 226 individuals (82.3% female, 17.7% male) received a three-minute exposure to Instagram images of women and men in the context of either hegemonic beauty ideals in the experimental group or body diversity in the control group. A conducted Mixed ANOVA with repeated measures showed significant group differences, including an increase in body dissatisfaction in the experimental group and a reduction in the control group after exposure. Statistically significant detrimental effects of exposure to images in the experimental group on women´s state mood as well as descriptive similar tendencies on men´s state mood were found. Moderating effects of the tendency to make upward social comparisons and the internalization of the gender-specific beauty ideal on the relationship between exposure content and the change scores of body dissatisfaction were found. Furthermore, a mediation model was calculated to investigate the effect of exposure content on post-measurement of body dissatisfaction, using the constructs "comparison processes regarding sexual attractiveness" and "assessment of one's own sexual attractiveness" as mediators. The model did not yield significant mediation, although significant relationships were found between the model components. Exploratory analyses were conducted on the influence of the assessment of one's own sexual attractiveness on related social comparisons and the intensity of engagement with Instagram content as a predictor of body dissatisfaction. The results highlight the relevance for psychoeducational purposes of addressing a critical engagement with depicted beauty ideals in social media. Moreover, the study proposes body diversity as an alternative content that can have a positive impact on body satisfaction, which can be actively sought during the individual Instagram user experience.